Effects of an intervention combining self‐care and self‐hypnosis on fatigue and associated symptoms in post‐treatment cancer patients: A randomized‐controlled trial. Issue 7 (24th April 2020) - Grégoire, Charlotte; Faymonville, Marie‐Elisabeth; Vanhaudenhuyse, Audrey; Charland‐Verville, Vanessa; Jerusalem, Guy; Willems, Sylvie; Bragard, Isabelle
Abstract: Objective: Cancer has a lot of consequences such as fatigue, sleep disturbances, emotional distress, cognitive impairment and reduced physical activity. Some hypnosis‐based psychological interventions showed positive effects on fatigue, sleep and emotional distress, but generally focused on breast cancer patients. Our study aimed at assessing the effects of a group intervention combining self‐care and self‐hypnosis on quality of life of cancer patients. Methods: Our longitudinal randomized‐controlled trial assessed the benefits of the intervention first on fatigue and secondly on associated symptoms (sleep, emotional distress, cognitive impairment and reduced physical activity) of post‐treatment cancer patients, and investigated predictors of the evolution of fatigue. All variables were measured with questionnaires and an actigraph (for sleep and physical activity). Results: Ninety five women with different cancers were included in our study. Group‐by‐time effects were showed for fatigue, sleep, emotional distress and cognitive functioning: symptoms have improved in the intervention group compared to wait‐list control group. Three predictors of the evolution of fatigue were revealed: depression, anxiety and worry. Conclusions: Our group intervention had benefits for post‐treatment cancer patients' quality of life. Impacting emotional distress could be important in order to decrease fatigue. Further studies are needed to replicate our results. This intervention could be easily implemented to improve quality of life of cancer patients. Registration: ClinicalTrials.gov (NCT03144154). Retrospectively registered on the 1st of May, 2017.